A new type of solar-system material recovered from Ordovician marine limestone - B. Schmitz (Nature Portfolio, 2016)
Meteorites falling on Earth today are believed to represent 100–150 parent bodies. Within 470 Myr ago sediments at a limestone quarry in Sweden, Schmitz et al. have found and identified a new type of meteorite based on chromium and oxygen isotopes sourced from a previously unknown parental body.